Observatories in space - World Book, Inc (Chicago, IL World Book, 2010)
An introduction to observatories in space with information about their history and use. Includes diagrams, fun facts, glossary, resource list, and index"--Provided by publisher
Includes bibliographical references (p. 62) and index
Hurg
5 8
Keywords: Astronomical instruments -- Juvenile literature; Astronomical observatories -- Juvenile literature